Sobre estados não-clássicos do campo eletromagnético quantizado - Ferreira, Cristino José dos Santos (2020)
We study a new state of a (single mode) quantized electromagnetic field, obtained from the superposition of coherent states over a semi-straight line in phase space. We evaluate its non-classicality through some indicators, for example, by the Wigner Function, W(x; p), the squeezing effect, and/or the sub-Poissonian statistic that this superposition may exhibit. In Wigner’s function the nonclassical character of the state usually reveals itself when it assumes less than zero values in certain regions of phase space, in which case it behaves more like a quasi-distribution of probabilities. The negativity of this function indicates the quantum character of the state it represents. This function is determined initially in terms of the number of superimposed coherent states aligned in the semi-straight line, the whole set expanded in Fock components. Then we include in the system the influence of gain and/or loss reservoirs in the Markovian approximation. Following, we study the evolution in time of the system to obtain a master equation involving the Wigner function, W(x; p; t), from which we obtain the temporal evolution of the mentioned non-classical properties. We illustrate possible schemes for the generation of such superposition, both in the case of trapped fields in microwave cavities and fields in traveling waveguides.